An Empirical Study of Motivation, Workload, and Occupational Stress on Nursing Performance - Farrel Diandra Siregar; Kosasih Kosasih; Ayu Laili Rahmiyati (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Nurses play a vital role in hospital services, yet high workload, job stress, and low motivation may reduce performance. This study aimed to analyze the effect of motivation, workload, and job stress on the performance of inpatient nurses at BaliMed Hospital Karangasem. The research used a quantitative approach with a descriptive-verificative design. The sample consisted of 71 nurses determined by saturated sampling. Data were collected using validated and reliable questionnaires, then analyzed with multiple linear regression. The results showed that motivation had a positive and significant effect on performance, while workload and job stress had negative and significant effects. Simultaneously, all three variables significantly affected performance with an R² value of 90.6%. The study concludes that motivation, workload, and job stress are dominant factors influencing nurse performance. It is suggested that hospital management improve motivation, balance workload, and manage stress through organizational support to maintain optimal service quality.